2017
DOI: 10.1038/srep44642
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric viruses between Rocio and West Nile: the role for Rocio prM-E proteins in virulence and inhibition of interferon-α/β signaling

Abstract: Mosquito-transmitted flavivirus Rocio (ROCV) was responsible for an outbreak of encephalitis in the Ribeira Valley, located in the south coast of Sao Paulo State, Brazil, in 1975–1976. ROCV also causes fatal encephalitis in adult mice. Seroprevalence studies in humans, horses and water buffaloes in different regions of Brazil have suggested that ROCV is still circulating in the country, indicating the risk of re-emergence of this virus. West Nile virus (WNV) is also a mosquito-transmitted encephalitic flavivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, it is still unclear how the virus is able to invade the CNS. Although our recent study has shown that the prM-E proteins of ROCV are responsible for neuroinvasion of ROCV and mortality in C57BL/6 mice [21], the exact residues in these proteins and the mechanisms responsible for neuropathogenesis of ROCV infection are still unknown. It is worth noting that ROCV was readily detected in olfactory bulbs 3 days after infection, suggesting that this may be a possible route for ROCV invasion into the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still unclear how the virus is able to invade the CNS. Although our recent study has shown that the prM-E proteins of ROCV are responsible for neuroinvasion of ROCV and mortality in C57BL/6 mice [21], the exact residues in these proteins and the mechanisms responsible for neuropathogenesis of ROCV infection are still unknown. It is worth noting that ROCV was readily detected in olfactory bulbs 3 days after infection, suggesting that this may be a possible route for ROCV invasion into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…ROCV (SPH 34675 strain) was passaged on Aedes albopictus (C6/36) cells and titrated by a plaque assay on BHK-21 cells as previously described [21].…”
Section: Virus and Cellsmentioning
confidence: 99%
“…The above DMS DNA amplicon was then used in equimolar amount with other ZIKV cDNA fragments and a linker fragment containing either mammalian CMV 12,16,17,19,20 or insect OpIE2 18 promoters in a CPER reaction to produce infectious DNA library as previously described 12 . The CPER-assembled infectious DNA library containing the CMV promoter was then transfected into Vero cells while the CPER-assembled infectious DNA library containing the OpIE2 promoter was transfected into C6/36 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The disease was mainly characterized by an acute onset of fever and headache, in addition to clinical signs and symptoms of central nervous system (CNS) involvement such as meningeal irritation, consciousness alterations and motor impairment [ 4 ]. The ability of ROCV to inhibit alpha/beta interferon (IFN-α/β) signaling may determine viral pathogenicity [ 5 ]. Surprisingly, no further cases of ROCV infection have been reported after this outbreak; however, serological surveys have suggested that unreported infections with ROCV among humans and animals in different regions of Brazil are still occurring [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%